Grammatical Alliance in the Acehian Language - Kartika, Rika; Mulyadi (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to describe the grammatical alliance system found in the Acehnese language. The research method used in this research is descriptive-qualitative. Miles and Huberman Model Qualitative Data Analysis Techniques Miles and Huberman can be carried out in three stages, namely data reduction, data display, and conclusion drawing and verification. Data was collected through online or offline searches, including from digital text databases and online sources, in Acehnese, namely Acehnese song lyrics. Comparison with relevant literature was also used to ensure the consistency and validity of the findings. Based on this, 16 lines were found in two Aceh-language regional songs. The data found that the Acehnese language belongs to the accusative type, which treats S the same as A and gives a gives a different treatment to P (S = A ≠ P).